Harmonizing Legal Pluralism in Marriage Laws: Policy Challenges on Child Marriage in Madura - Mohsi, Mohsi; Romli, Muhammad; Zakaria, Soni; Fudholi, Moh. (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2025)
This research examines the persistence of child marriage in the Madura region through the lens of legal pluralism, particularly the intersections of Islamic, customary, and state laws. Although religious and cultural practices continue to shape norms and values, they often counteract statutory provisions designed to safeguard children's rights. Proposed is a harmonization model that integrates fiqh and customary law with national law, providing cultural legitimacy while protecting children at the same time. Adopting the socio-legal qualitative approach, the research uses a combination of normative legal theory and empirical research conducted in Sampang Regency, which embraced interviews and documentation of court decisions, fatwas, local regulations, and case files on child marriage, with religious leaders, elders, lawyers, judges, parents, and child marriage survivors. Spradley’s ethnographic model guided the analysis in documenting core cultural themes and their components. It is cultural and religious rationalization, along with ignorance of laws and weak enforcement, that continue to allow child marriage. Solid legal reform requires improving child protection by local leaders, educating children's rights, and reframing marriage-age laws from religious prohibitions to administrative restrictions. It gaps legal pluralism and children's rights by cohesive laws, socio-cultural practices, and international human rights.